2008
DOI: 10.1063/1.2920210
|View full text |Cite
|
Sign up to set email alerts
|

Low thermal conductivity and high thermoelectric figure of merit in n-type BaxYbyCo4Sb12 double-filled skutterudites

Abstract: Filled skutterudites are one of the most promising thermoelectric materials for power generation applications. The choice and concentration of filler atoms are key aspects for achieving high thermoelectric figure of merit values. We report on the high temperature thermoelectric properties in the double-filled skutterudites BaxYbyCo4Sb12. The combination of Ba and Yb fillers inside the voids of the skutterudite structure provides a broad range of resonant phonon scattering and consequently a strong suppression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
245
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(258 citation statements)
references
References 22 publications
11
245
1
1
Order By: Relevance
“…As mentioned above, Yb is an indispensable filler for high-performance n-type skutterudites, as indicated for previously reported double-or triple-filled samples. 5,52 Yb-filled CoSb 3 actually possesses comparable κ L values to those of double-or triple-filled CoSb 3 considering the experimental error and different C p used for κ calculations, as shown in Supplementary Figure S4. The intrinsically low κ L of Yb-filled CoSb 3 can be well understood from the specific features of its phonon dispersion, as shown in Figure 6d.…”
Section: Te Transport Propertiesmentioning
confidence: 99%
“…As mentioned above, Yb is an indispensable filler for high-performance n-type skutterudites, as indicated for previously reported double-or triple-filled samples. 5,52 Yb-filled CoSb 3 actually possesses comparable κ L values to those of double-or triple-filled CoSb 3 considering the experimental error and different C p used for κ calculations, as shown in Supplementary Figure S4. The intrinsically low κ L of Yb-filled CoSb 3 can be well understood from the specific features of its phonon dispersion, as shown in Figure 6d.…”
Section: Te Transport Propertiesmentioning
confidence: 99%
“…To achieve high ZT values in TE materials, a synergistic optimisation on both transport aspects is required. Armed with a deep understanding of transport phenomena, spectacular enhancements in the figure of merit ZT have been achieved in recent years across many families of TE materials, 22,31,38,54,69,104,109,124,132,150, as shown in Figure 10. Many traditional TE materials have doubled their ZT and new promising material systems have been identified and optimised.…”
Section: Synergistic Optimisation For High Ztsmentioning
confidence: 99%
“…Experimentally, the so-designed multiple-filled skutterudites do possess reduced κ L and enhanced ZT values, as shown in refs. 68,69,132,133. Resonant frequencies of fillers in p-type skutterudites were also calculated by Liu et al 134 and used to design high-performance p-type skutterudites.…”
Section: From the Conventional Phonon-phonon Interactions To Nanostrumentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recently, filling two or more types of fillers into the voids in skutterudite have been shown to be able to further reduce lattice thermal conductivity and improve ZT to 1.4 in double-filled and 1.7 in multiple-filled n-type skutterudites. [17][18][19][20] Although there are a series of recent study reported with very high ZTs in n-type partially filled skutterudites, only a few literatures focusing on high temperature thermoelectric properties in p-type skutterudites have been published in the past decade. Furthermore, the ZT values in p-type filled skutterudites are confirmed in experiment around 1.0, much lower than n-type materials.…”
Section: Introductionmentioning
confidence: 99%